2000
DOI: 10.1243/0959651001540519
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of axial piston pump pressure ripple

Abstract: The reduction in source flow ripple in hydraulic systems is the most effective method of reducing pump-generated pressure ripple and system noise. This paper describes reductions in axial-piston pump delivery flow ripple achieved using a novel timing mechanism which is inherently speed, flow and pressure sensing. Fixed-speed tests have shown that the mechanism can significantly reduce axial-piston pump delivery flow ripple over a wide range of delivery pressures and pump displacements. Furthermore, the reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 1 publication
1
42
0
Order By: Relevance
“…The axial piston pump including nine pistons is driven by a variable-speed motor. One noticeable point is that the source flow ripple radiated from the axial piston pump can interact with the characteristics of the hydraulic circuit to produce pressure pulsations in the hydraulic energy system [22][23][24]. The pressure pulsations are transmitted from the source (pump) through the servo-valve to the oil tank.…”
Section: Transmission Of the Pressure Pulsations Inside A Hydraulic Ementioning
confidence: 99%
See 1 more Smart Citation
“…The axial piston pump including nine pistons is driven by a variable-speed motor. One noticeable point is that the source flow ripple radiated from the axial piston pump can interact with the characteristics of the hydraulic circuit to produce pressure pulsations in the hydraulic energy system [22][23][24]. The pressure pulsations are transmitted from the source (pump) through the servo-valve to the oil tank.…”
Section: Transmission Of the Pressure Pulsations Inside A Hydraulic Ementioning
confidence: 99%
“…The pump parameters such as the pump speed, piston number and maximum supply pressure greatly affected the pressure pulsations of the hydraulic energy system and its components in practice [20][21][22]. However, from the previous works, it can be seen that the self-excited (squeal) noise of the servo-valve has been paid little attention in their studies since it was hardly excited by the servo-valve in the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…While some works focus on reducing internal sources of SBN [2], the main focus in most research on noise in hydraulic pumps is on reducing the magnitude of the pressure ripple oscillations at the outlet port [3][4][5][6][7][8]. For EGMs, this effort has resulted in the formulation of design solutions that involve tooth profile modifications able to reduce the kinematic flow oscillations: Manring and Huang formulated criteria suitable for standard involute designs [6,9]; Negrini introduced the so-called dual-flank principle, a zero-backlash solution currently adopted by several manufacturers that permits to increase the number of displacement chambers [4] to reduce the flow oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…The research group led by Palmberg set a precompression volume in valve plate between the discharged kidney slot and sucked kidney slot [17]. They found that small precompression volume can amazingly lessen enormous problems of noise, pulsation, and hydraulic impact [18,19]. And an axial piston pump's valve plate which adopts a prepressurization fluid path consisting of a damping hole, a buffer chamber, and an orifice can reduce flow ripple to some extent [20].…”
Section: Introductionmentioning
confidence: 99%